2017
DOI: 10.1016/j.jrras.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Uranium and other heavy toxic elements distribution in the drinking water samples of SW-Punjab, India

Abstract: Available online xxxKeywords: Radionuclide Uranium Radiological risk Toxicity Laser a b s t r a c tIn the present investigations, Laser Fluorimetry technique has been used for the microanalysis of uranium content in drinking water samples collected from different sources like the hand pumps, tube wells of various depths from wide range of locations in the four districts of SW-Punjab, India. The purpose of this study was to investigate the uranium concentration levels of ground water being used for drinking pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(70 citation statements)
references
References 23 publications
4
63
3
Order By: Relevance
“…Also, the geological formation of the area is known to be associated with elevated concentrations of radionuclides (Olurin et al, 2012;Farai and Vincent 2006). Similar studies have confirmed same in other part of the world (Bajwa et al, 2015;Jurgens et al, 2010;Believermis et al, 2009;UNSCEAR, 2000). The type and values of radionuclides recorded in Table 1 conform well to literature.…”
Section: Discussion On Activity Concentrations Of the Water Samplessupporting
confidence: 61%
“…Also, the geological formation of the area is known to be associated with elevated concentrations of radionuclides (Olurin et al, 2012;Farai and Vincent 2006). Similar studies have confirmed same in other part of the world (Bajwa et al, 2015;Jurgens et al, 2010;Believermis et al, 2009;UNSCEAR, 2000). The type and values of radionuclides recorded in Table 1 conform well to literature.…”
Section: Discussion On Activity Concentrations Of the Water Samplessupporting
confidence: 61%
“…During summer, the Fe was found in the range of 0.009-5.41mg/L while in winter it ranged from 0.074 to 7.7mg/L. The mean iron concentration of water samples in the study area were higher than those reported by Bajwa et al (2015) in SW Punjab (0.83 mg/L). Figure 2 shows the concentration of arsenic in groundwater of the study area in two different seasons.…”
Section: Iron and Arseniccontrasting
confidence: 53%
“…Average annual rainfall in this zone is about 420 mm. The soil of the study area is loose, sandy, calcareous and alluvial, which is an admixture of gravel, sand, silt and clay in varying proportions (Bajwa et al 2015). Physiographically, the region has about flat to undulating geography and little patches of sand dunes.…”
Section: Study Areamentioning
confidence: 99%
“…Due to potential hazards attributed to use of uranium enriched water, the interest in study of uranium in groundwater has increased tremendously. Previous study reported high uranium levels in SW region of Punjab (Bajwa et al, 2015). Punjab, one of the wealthiest states of India is economically based on agriculture and it has been reported that 75% of total pesticides used in Punjab is just devoured by Malwa region which covers only 15 percent land area of Punjab (Mittal et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…use of fertilizers in the agriculture lands and due to squanders discharged from factories or thermal power plants in this region(Bajwa et al 2015). Since an extensive concentration of bicarbonate and phosphate have also been observed in groundwater samples of SW Punjab(Tripathi et al2012), may be reason for high concentration observed in groundwater samples from shallow depths as phosphate and bicarbonates (salinity) present in soil enhance the leaching and mobility of uranium.Overall, the quite higher uranium levels observed in water samples of the SW-Punjab region may be due to anthropogenic activities.…”
mentioning
confidence: 95%